The Need to Set a Fiscal Target and Improve the Fund Governance Structure of the National Pension in Korea - Heesuk Yun; Dohyung Kim; Jonghoon Kim (Korea Development Institute (KDI), 2015)
Setting an explicit fiscal target in the pension system and implementing stronger fund governance are needed to address the concerns regarding the projected rise and fall of the National Pension Fund in Korea. Strengthening expertise and accountability of the fiduciaries is essential for a better governance structure, but their role must be confined by the mandate derived in part from the fiscal target of the pension system. Hence, setting the fiscal target, which provides a link between the pension system and pension fund governance, may be the first step to advancing the governance structure of the National Pension Fund. - Enhancing expertise and accountability is imperative in reforming the governing body, which should be accountable for long-term investment performance necessary to meet the National Pension's fiscal target. - The National Pension Fund has built up to 32.7% of market capitalization or 28.3% of domestic bonds outstanding. It is expected to grow further before it is rapidly liquidated and depleted. - Passive and trend-chasing investment behavior prevails in the accumulation phase of the NPF where risk-taking can be desirable. - A 5.2% rate of return of the NPF is well below the double-digit rate of returns achieved by other comparable public pension funds such as the CPPIB and CalPERS. - Better fund governance is associated with better investment performance possibly due to more efficient asset allocation. - The mandate given to the NPF is unclear due to the lack of a long-term fiscal target for the pension system for which reform has been delayed. - Committee members are often unable to understand proposed investment strategies and thus reluctant to adjust the existing asset allocation. - Absenteeism is common especially among ex-officio members, who attend one in every six meetings. - The Ministry of Health and Welfare both proposes and approves the fund management plan although the Committee is nominally responsible for the approval. - A clear mandate should be given to the independent governing body, which in turn is accountable for the given mandate. - The Committee must be stand-alone and responsible for the Fund Investment Office, which currently belongs to the NPS, a government agency. - Previous reform proposals were discarded due to the popular suspicion that the governing body controlled by financial experts may take excessive risks or seek their own interests and not those of contributors and beneficiaries.
Keywords: 330